MENINGKATKAN KEMAMPUAN BERBICARA PADA PELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN METODE SOSIODRAMA SISWA KELAS V SD NEGERI 104214 DELI TUA - Erlinda Simanungkalit (FIP Unimed, 2017)
The purpose of this study is to improve students' speaking ability by applying the sociodrama method through learning Indonesian in grade V SD Negeri 104214 Deli Tua. This type of research is collaborative action research (PTK). Data collection methods used are observation, and documentation. Based on observation result of first ability of researcher with teacher of class 38 people from 26 students there are 5 students who able to speak with percentage (13,1%) and 33 students who have not able to speak with percentage (86,9%), with mean value Class 23.68. Keywords: Ability, Speaking, Sociodrama